Identifying and Managing Intraoperative Arrhythmia: A Multidisciplinary Operating Room Team Simulation Case - Praelada Wongsirimeteekul; Christine L. Mai; Emil Petrusa; Rebecca Minehart; Maureen Hemingway; May Pian-Smith; Ersne Eromo; Roy Phitayakorn (Association of American Medical Colleges, 2018)
Introduction Resuscitation of a critically ill patient is challenging for both novice learners and experienced health care providers. During a critical event, not only is it important to identify the correct underlying diagnosis, it is equally crucial that the appropriate Advance Cardiac Life Support algorithm, medications, and defibrillator modality are implemented. This scenario features a 56-year-old female who presents for excisional biopsy of an inguinal lymph node to evaluate lymphadenopathy concerning for lymphoma. Intraoperatively, she goes into cardiopulmonary arrest. Participants must identify and manage three different scenarios: (1) ventricular fibrillation, (2) unstable ventricular tachycardia, and (3) bradycardia, including the use of the defibrillator. Method Weekly simulation sessions were conducted in the in situ simulation operating room at Massachusetts General Hospital. Surgical residents, anesthesiology residents, nurses, and surgical technicians participated in a multidisciplinary operating room team. Each approximately 60-minute session included an orientation, the case, and the debriefing. Equipment included a simulation operating room with general surgery supplies, general anesthesia equipment, a high-fidelity SimMan patient simulator, a code cart, and a defibrillator. Results Ninety-one multidisciplinary participants completed this scenario from September to December 2015. Participants reported that the scenario was applicable to their clinical practice (96%), promoted teamwork skills (88%), and encouraged interprofessional learning (94%). Discussion Intraoperative cardiac arrest is a devastating event that can result in poor patient outcomes if the care team is not thoroughly prepared for crisis management. This simulation case scenario was implemented to train multidisciplinary learners in the identification and management of such an event.